2021
DOI: 10.1002/pchj.464
|View full text |Cite
|
Sign up to set email alerts
|

The origin of Vierordt's law: The experimental protocol matters

Abstract: In 1868, Karl Vierordt discovered one type of errors in time perception-an overestimation of short duration and underestimation of long durations, known as Vierordt's law. Here we reviewed the original study in its historical context and asked whether Vierordt's law is a result of an unnatural experimental randomization protocol. Using iterative Bayesian updating, we simulated the original results with high accuracy. Importantly, the model also predicted that a slowly changing random-walk sequence produces les… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 33 publications
5
65
1
Order By: Relevance
“…According to the model, for these participants, the overall central tendency bias should be smaller, if the stimuli are indeed similar from trial to trial. This was validated by showing in our previous study (Glasauer & Shi 2021), that the central tendency in sequences with complete random stimulus order was larger than in sequences with random-walk fluctuation. Here we showed that this decrease in central tendency and, more importantly, the remaining central tendency, is well-predicted by the two-state model.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…According to the model, for these participants, the overall central tendency bias should be smaller, if the stimuli are indeed similar from trial to trial. This was validated by showing in our previous study (Glasauer & Shi 2021), that the central tendency in sequences with complete random stimulus order was larger than in sequences with random-walk fluctuation. Here we showed that this decrease in central tendency and, more importantly, the remaining central tendency, is well-predicted by the two-state model.…”
Section: Discussionsupporting
confidence: 58%
“…2C, red time course, for an example of such a random walk). As explained in our previous paper (Glasauer & Shi 2021), this condition tests the prediction of the simple iterative and the Petzschner & Glasauer (2011) explanatory models, which both predict that the central tendency vanishes in the random walk condition. However, while it was found that the central tendency indeed decreased substantially and was significantly smaller during random walk (t-test, n=14, p<0.0001; see Fig.…”
Section: Experimental Validation Of Serial Dependence and The Two-state Modelmentioning
confidence: 65%
See 2 more Smart Citations
“…Although it is not straightforward to empirically dissociate linear versus logarithmic encoding of time, some psychophysical [32][33][34] and neurophysiological evidence [35] suggests a logarithmic encoding of time. Moreover, several Bayesian models of time estimation have assumed that Bayesian integration takes place on a logarithmic scale [36][37][38], which naturally accounts for lognormally distributed time estimates and the scalar property. The MLN model departs from these logarithm-based Bayesian models in two theoretically important ways: (i) assumptions about the scalar property and (ii) the scale at which Bayesian integration is applied: logarithmic or linear.…”
Section: First Theoretical Consideration: Shape Of the Priormentioning
confidence: 99%